Long term NDVI patterns of Pinus sp., Salix sp. and Populus sp. forest stands in the Lower Delta of the Paraná River (Argentina). - Piani, Virginia; Zamboni, Lisandra P.; Viva Mayer, Francisco; F. Sione, Walter; G. Aceñolaza, Pablo (BOSQUE, 2023)
Plantation forest constitute one of the main productive activities of the Lower Delta of the Paraná River. The environment correspond to a wetland in which hydrological processes are a fundamental part of the landscape dynamics. However, forestation is also characterized for generating different impacts on this dynamic, which must be known for effective environmental management. In this context, it is useful to specify the relationships between different structural and functional attributes of the tree cover and those derived from satellite images. Therefore, the aim of this paper was to characterize and to analyze the Normalized Differential Vegetation Index (NDVI) patterns in Pinus sp., Salix sp. and Populus sp. forestations of the Paraná River Delta with a multitemporal approach. For this we used medium spatial resolution satellite images for the period 2008 to 2018. NDVI patterns were analyzed through the use of Geographic Information Systems and Google Earth Engine algorithms. NDVI records, by species and by date, were used to generate seasonal, annual and monthly time series. The plantations showed a markedly seasonal response, with lower values in winter and higher values in spring/summer. Pinus sp. showed mean annual NDVI values higher than Populus sp. and Salix sp, according to its perennial (Pinus sp.) and semi-deciduous (Salicaceae) characteristics. New information and methodologies on the spectral responses of forestation in the region was obtained from large volumes of data available in the Cloud, which made it possible to know in detail the NDVI phonological pattern of different types of forestation.